An Exploration of the Relationship between Police Presence, Crime, and Business in Developing Countries - Islam, Asif (World Bank, Washington, DC, 2016)
Economic theory predicts that a rise in police presence will reduce criminal activity. However several studies in the literature have found mixed results. This study adds to the literature by exploring the relationship between the size of the police force and crime experienced by firms. Using survey data for about 12,000 firms in a cross-section of 27 developing countries, the study finds that increasing the size of the police force is negatively associated with crime experienced by firms. The results are confirmed using a panel of firms for a subset of countries for which data are available. The study also finds that this negative relationship is stronger under certain macro-economic circumstances.